Ответ:
............
Объяснение:
...........
(-32; 38)
{х/3 + у/3 = 2 | * -6
{х/22 + у/11 = 2 | * 22
{-2х - 2у = -12
{х + 2у = 44
{-х = 32
1)
-х = 32
х = -32
2)
х + 2у = 44
-32 + 2у = 44
2у = 44 - (-32)
2у = 44 + 32
2у = 76
у = 76 : 2
у = 38
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
............
Объяснение:
...........
Ответ:
(-32; 38)
Объяснение:
{х/3 + у/3 = 2 | * -6
{х/22 + у/11 = 2 | * 22
{-2х - 2у = -12
{х + 2у = 44
{-х = 32
{х + 2у = 44
1)
-х = 32
х = -32
2)
х + 2у = 44
-32 + 2у = 44
2у = 44 - (-32)
2у = 44 + 32
2у = 76
у = 76 : 2
у = 38